library environment and equipments for the education of the visually impaired in Nigeria. (2001)
This study specifies what the library environment for the blind should be in terms of space, furniture and equipment. In conclusion, it suggests for a need to embark on researches on the advancement as it pertains to blind peoples access to information technology in Nigeria.